Liquid nitrogen quenching of lead-doped "2212" bismuth superconductors - I. M. Tang (2018)
The effects of lead substitution in Bi 4 Sr 4 Ca 2 Cu 4 O y conductors are studied. Liquid nitrogen quenching of the compounds Bi 4-x Pb x Sr 4 Ca 2 Cu 4 O y (x=0.7, 0.9, 1.0, 1.1 and 1.2) is required to produce superconductors having T c 's well above the transition temperature of the host "2212" superconductor. The X-ray diffraction patterns of these compounds are those of the "2212" structure (with a few weak lines of the "2223" structure appearing). The resistivity curve for the lighter doped compounds (x=0.7 and 0.9) indicates the existence of two super-conducting phase transitions, one at around 105 K and another around 89 K. For the heavier doped compounds (x=1.1 and 1.2), the resistivity curves show only a single transition. In general, the zero resistivity temperatures are seen to decrease with increased Pb doping. © 1990.